1992
DOI: 10.1115/1.2911908
|View full text |Cite
|
Sign up to set email alerts
|

Evaporation of Single Drops of n-Pentane/n-Hexane Mixtures in Water

Abstract: The evaporation of isolated drops (2.1−3.0 mm diameter) of nonazeotropic n-pentane/n-hexane mixtures in the medium of water was observed under pressures of 0.11−0.46 MPa and temperature differences up to 27 K. The mole fractions of n-pentane, x, in the mixtures were set at 0.9, 0.5, 0.1, and 0, to be completed by the condition x = 1 set in a preceding work (Shimaoka and Mori, 1990). Experimental results are presented in terms of the instantaneous rise velocity of, and an expression of instantaneous heat transf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2006
2006
2012
2012

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…This phenomena can also be proved by means of visualization test (see Fig.4 Run4 t=80ms). Two series of tests were achieved beside the centerline of jet, i.e., series 2 tests (point 5,6,7,8) which were for 2mm apart from the centerline and series 3 tests (point 9,10,11,12) which were for 5mm apart from the centerline. The two series of tests showed that no liquid ethanol existed and the jet mainly contained the ethanol vapor or cooled FC-3283 droplets.…”
Section: Temperature Distribution Around Ethanol Jetmentioning
confidence: 99%
See 1 more Smart Citation
“…This phenomena can also be proved by means of visualization test (see Fig.4 Run4 t=80ms). Two series of tests were achieved beside the centerline of jet, i.e., series 2 tests (point 5,6,7,8) which were for 2mm apart from the centerline and series 3 tests (point 9,10,11,12) which were for 5mm apart from the centerline. The two series of tests showed that no liquid ethanol existed and the jet mainly contained the ethanol vapor or cooled FC-3283 droplets.…”
Section: Temperature Distribution Around Ethanol Jetmentioning
confidence: 99%
“…Tadrist et al [10] investigated the heat transfer characteristics on n-pentane/water counter-current system. Shimaoka and Mori [11] experimentally investigated the evaporating heat transfer of n-pentane/n-hexane mixture heated by water. However, these works focused on the evaporation of the liquid droplets in another liquid flow.…”
Section: Introductionmentioning
confidence: 99%